The Impact of Crystal Growth Temperature on Zr Reach Crystalline Phase Formation in a Nuclear Waste Confinement Glass Ceramic - Moudir, Dalila; Kamel, Nour-El-Hayet; Benmounah, Abdelbaki; Mouheb, Yasmina; Souag, Rafika; Bezzazi, Boudjmaa; Aouchiche, Fairouz; Kamel, Ziane; Kamariz, Soumia (Newest Updates in Physical Science Research Vol. 9, 2021)
Many glass ceramics could be used to contain radioactive waste. This is the case with glasses that contain radiation-resistant ceramics such as zirconolites, pyrochlores, or pyroxenes. This study investigates the effect of crystal growth temperature on the formation of the following phases in a nuclear glass ceramic system: Al2O3-SiO2-CaO-MgO-ZrO2-TiO2. The materials with six contents of ZrO2, ranging from 1.00 to 6.40 m.%, are synthesized by a discontinuous method, consisting in a double-melting at 1,350°C, followed by both a nucleation at 564°C, and a crystal growth treatment at: 900, 100 and 1,100°C. The morphology of the materials as a whole reveals a glassy feature with an opaque aspect. A different crystallisation process can also be seen from the bulk to the surface. The X-ray diffraction (XRD) analysis of glass ceramics reveals that the main identified crystalline skeletons are those of 2M-zirconolite, CaZrTi2O7, and ZrO2, depending on the ZrO2 content of the materials and the crystal-growth temperature. Due to the complexity of the oxide mixture, the material with the middle content in ZrO2 (4.5 m. %) and crystallised at the middle value of Tc (1,010°C) shows the greatest content in zirconolite (87%), doped with either lanthanides or alcalin-earth elements.The temperature of 1,010°C appears to be more selective in terms of 2M-zirconolite formation.